2002
DOI: 10.1046/j.1445-5994.2002.d01-28.x
|View full text |Cite
|
Sign up to set email alerts
|

Minidose (1 mg) warfarin as prophylaxis for central vein catheter thrombosis

Abstract: This study found no benefit of the routine use of minidose warfarin for prophylaxis of central vein' catheter thrombosis in patients with haematological malignancies and therefore does not support the routine use of minidose warfarin for prophylaxis in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 15 publications
0
91
0
3
Order By: Relevance
“…Using the specified selection criteria, a total of nine prospective studies of thromboprophylaxis use in adult cancer patients with CVC were identified (Table 1) (Bozzetti et al, 1983;Bern et al, 1990;Monreal et al, 1996;Nightingale et al, 1997;Boraks et al, 1998;Heaton et al, 2002;Mismetti et al, 2003;Couban et al, 2005;Verso et al, 2005). Of these studies, one investigated unfractionated heparin thromboprophylaxis, (Bozzetti et al, 1983) while another three studied the efficacy of different low molecular weight heparin preparations (dalteparin, nadroparin and enoxaparin, respectively) (Monreal et al, 1996;Mismetti et al, 2003;Verso et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the specified selection criteria, a total of nine prospective studies of thromboprophylaxis use in adult cancer patients with CVC were identified (Table 1) (Bozzetti et al, 1983;Bern et al, 1990;Monreal et al, 1996;Nightingale et al, 1997;Boraks et al, 1998;Heaton et al, 2002;Mismetti et al, 2003;Couban et al, 2005;Verso et al, 2005). Of these studies, one investigated unfractionated heparin thromboprophylaxis, (Bozzetti et al, 1983) while another three studied the efficacy of different low molecular weight heparin preparations (dalteparin, nadroparin and enoxaparin, respectively) (Monreal et al, 1996;Mismetti et al, 2003;Verso et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, one investigated unfractionated heparin thromboprophylaxis, (Bozzetti et al, 1983) while another three studied the efficacy of different low molecular weight heparin preparations (dalteparin, nadroparin and enoxaparin, respectively) (Monreal et al, 1996;Mismetti et al, 2003;Verso et al, 2005). Use of minidose warfarin (1 mg daily) was studied in six independent trials, incorporating 1463 patients (Bern et al, 1990;Nightingale et al, 1997;Boraks et al, 1998;Heaton et al, 2002;Mismetti et al, 2003;Couban et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some early open-label trials suggested a benefit from oral, low-dose daily warfarin 83 or daily SC dose of LMWH, 84 more recent double-blind, placebo-controlled RCTs did not find any advantages for either of these prevention strategies. [85][86][87] The choice to start prophylaxis against venous thromboembolic events in all oncology patients bearing a CVC, either with LMWH or with minidose warfarin, remains unsupported by evidence-based medicine.…”
Section: Thrombosismentioning
confidence: 99%